2012
DOI: 10.1088/0004-637x/754/2/98
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oxygen Abundances for Low-Luminosity LVL Galaxies

Abstract: We present MMT spectroscopic observations of H II regions in 42 low luminosity galaxies in the Spitzer Local Volume Legacy (LVL) survey. For 31 of the 42 galaxies in our sample, we were able to measure the temperature sensitive [O III] λ4363 line at a strength of 4σ or greater, and thus determine oxygen abundances using the "direct" method. Our results provide the first "direct" estimates of oxygen abundance for 19 of these galaxies. "Direct" oxygen abundances were compared to B -band luminosities, 4.5 µm lumi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

68
534
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(607 citation statements)
references
References 144 publications
(171 reference statements)
68
534
4
1
Order By: Relevance
“…We also show the XMD emission-line galaxies with 12 + log O/H ≤ 7.35 by and Izotov et al (2012) in small red filled circles. The small open squares in magenta, green, and blue are the data derived by Berg et al (2012), Pustilnik et al (2011), andJames et al (2015), respectively (see text). The most-metal deficient BCDs I Zw 18, SBS 0335-052W, and SBS 0335-052E are shown with filled blue triangles and are labelled.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also show the XMD emission-line galaxies with 12 + log O/H ≤ 7.35 by and Izotov et al (2012) in small red filled circles. The small open squares in magenta, green, and blue are the data derived by Berg et al (2012), Pustilnik et al (2011), andJames et al (2015), respectively (see text). The most-metal deficient BCDs I Zw 18, SBS 0335-052W, and SBS 0335-052E are shown with filled blue triangles and are labelled.…”
Section: Resultsmentioning
confidence: 99%
“…The position of all XMD candidates from this paper and from and Izotov et al (2012) are also plotted. Berg et al (2012) studied a sample of 42 low-luminosity galaxies aiming to fill the relatively sparse low-luminosity end of the relation with intrinsically faint galaxies. For comparison we show their data in small open squares in magenta.…”
Section: Luminosity-metallicity Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we compare their metallicities with that expected from the relation derived for the Local Volume dwarfs with well-known distances and O/H by Berg et al (2012). The scatter in this relation is quite small, σ (O/H) =0.15 dex.…”
Section: Gas Phase Metallicitiesmentioning
confidence: 80%
“…The heavy element content of star-forming galaxies is characterized by a strong relation between the stellar mass and average gas-phase oxygen abundance (Lequeux et al 1979;Tremonti et al 2004). This so-called mass-metallicity relation (MZR) extends to low stellar mass galaxies (∼ 10 7 M⊙ Lee et al 2006;Zahid et al 2012a;Berg et al 2012) and is observed at intermediate (Savaglio et al 2005;Cowie & Barger 2008;Zahid et al 2011;Moustakas et al 2011;Zahid et al 2013a) and high redshifts (Erb et al 2006;Mannucci et al 2009;Laskar et al 2011). The metallicity at all stellar masses increases with time and the high mass end of the relation flattens at late times as galaxies enrich to an empirical upper limit in the gas-phase abundance (Zahid et al 2013a).…”
Section: Introductionmentioning
confidence: 89%